2012
DOI: 10.9790/3008-0260108
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxic Activity of Essential Oil from Nutmeg (Myristica Fragrans) Against Tetrachloride-Induced Hepatic Damage In Mice

Abstract: To extracting and purifying the essential oil containing terpenes from dried seeds of nutmeg Myristica fragrans available in Iraqi markets. Male albino mice (n= 44), with average weight (25-28 g) of about six weeks old The study also employed an in vivo evaluation of the hepatotoxic effect of essential oil in male albino mice at different concentrations (500 and 1000 mg / kg) given orally for 7 days including biochemical functions serum glutamic pyruvic transaminase (SGPT),serum glutamic oxaloacetic transamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…These results are in agreement with the obtained by (28). Nutmeg treated mice showed statistically significant alteration in the biochemical indicators of liver function including significant elevation in AST, ALT, ALP and TSB in a dose dependent manner.…”
Section: Each Value Is Represented As Mean ± Standard Deviation (N = ...supporting
confidence: 92%
“…These results are in agreement with the obtained by (28). Nutmeg treated mice showed statistically significant alteration in the biochemical indicators of liver function including significant elevation in AST, ALT, ALP and TSB in a dose dependent manner.…”
Section: Each Value Is Represented As Mean ± Standard Deviation (N = ...supporting
confidence: 92%
“…This observation corroborated earlier findings of Ugwuja et al 26 who observed that concurrent administration of garlic and ginger at culinary dose exerts beneficial effects on plasma glucose and lipids in health and diseases. Although several studies have examined the potentials of individual spices in ameliorating Cd toxicity, 12,16,24 the present study seems to be the first to examine the role of spices mixture in mitigating Cd-induced organ damage.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, apart from its protective effect on oxidative stress in hypercholesterolaemic rats reported by Hassanen,15 nutmeg has been associated with hepatotoxic activity and intoxication. 16,17 Considering that spices are usually used as mixtures and based on the fact that garlic, ginger and nutmeg have protective effects against oxidative stress, apoptosis, ischemia and inflammation which are implicated in cadmium-induced toxicity, this study aims to investigate the potential protective effect of spice mixture containing garlic, ginger and nutmeg on the liver and kidney of cadmium exposed rats.…”
Section: Introductionmentioning
confidence: 99%